Application of data assimilation for parameter correction in super cavity modelling - Ha, Tran Thu; Son, Nguyen Anh; Hai, Duong Ngoc; Phong, Nguyen Hong (Vietnam Journal of Science and Technology, 2016)
On the imperfect water entry, a high speed slender body moving in the forward direction rotates inside the cavity. The super cavity model describes the very fast motion of body in water. In the super cavity model the drag coefficient plays important role in body’s motion. In some references this drag coefficient is simply chosen by different values in the interval 0.8-1.0. In some other references this drag coefficient is written by the formula with is the cavity number, is the angle of body axis and flow direction, is a parameter chosen from the interval 0.6-0.85. In this paper the drag coefficient is written with fixed and the parameter is corrected so that the simulation body velocities are closer to observation data. To find the convenient drag coefficient the data assimilation method by differential variation is applied. In this method the observing data is used in the cost function. The data assimilation is one of the effected methods to solve the optimal problems by solving the adjoin problems and then finding the gradient of cost function.